Pseudomonas aeruginosa ventilator-associated pneumonia management - Ramírez-Estrada S (Infection and Drug Resistance, 2016)
Sergio Ramírez-Estrada,1 Bárbara Borgatta,1,2 Jordi Rello3,4 1Critical Care Department, Vall d'Hebron University Hospital, 2CRIPS, Vall d'Hebron Institute of Research (VHIR), 3Department of Medicine, Universitat Autònoma de Barcelona (UAB), Barcelona, 4Centro de Investigación Biomédica en Red Enfermedad Respiratoria – CIBERES, Madrid, Spain Abstract: Ventilator-associated pneumonia is the most common infection in intensive care unit patients associated with high morbidity rates and elevated economic costs; Pseudomonas aeruginosa is one of the most frequent bacteria linked with this entity, with a high attributable mortality despite adequate treatment that is increased in the presence of multiresistant strains, a situation that is becoming more common in intensive care units. In this manuscript, we review the current management of ventilator-associated pneumonia due to P. aeruginosa, the most recent antipseudomonal agents, and new adjunctive therapies that are shifting the way we treat these infections. We support early initiation of broad-spectrum antipseudomonal antibiotics in present, followed by culture-guided monotherapy de-escalation when susceptibilities are available. Future management should be directed at blocking virulence; the role of alternative strategies such as new antibiotics, nebulized treatments, and vaccines is promising. Keywords: multidrug-resistant, ICU, new-antibiotics, adjunctive-therapies, care-bundles